TECHNICAL ISSUES ON DEVELOPING STUDENTS’ SOCIAL POWER THROUGH IDEOLOGICAL EDUCATION AT HIGHER EDUCATION - Kodirov, Q.A. (FAN va JAMIYAT, 2021)
This article is aimed at identifying technological issues of the formation of students social powers in the higher education system, as well as factors that negatively affect the training of competitive specialists in the educational process.